2015
DOI: 10.1139/cjpp-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of kisspeptin on the regulation of vascular tone

Abstract: Kisspeptin has been implicated in cardiovascular control. Eicosanoids play a crucial role in the activation of platelets and the regulation of vascular tone. In the present study, we investigated the effect of kisspeptins on eicosanoid synthesis in platelets and aorta in vitro. Platelets and aorta were isolated from Wistar-Kyoto rats. After preincubation with different doses of kisspeptin, samples were incubated with [1-(14)C]arachidonic acid (0.172 pmol/mL) in tissue culture Medium 199. The amount of labeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 28 publications
1
13
2
Order By: Relevance
“…31 KPs also regulate vascular tone as a constrictor. 32 However, in our study, chronic infusion of KP-10 did not affect body weight, plasma glucose level, and BP in ApoE À/À mice. Pentraxin-3 is well known to reflect vascular inflammation derived from mainly ECs followed by VSMCs and macrophages and also is associated with apoptosis and plaque vulnerability.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…31 KPs also regulate vascular tone as a constrictor. 32 However, in our study, chronic infusion of KP-10 did not affect body weight, plasma glucose level, and BP in ApoE À/À mice. Pentraxin-3 is well known to reflect vascular inflammation derived from mainly ECs followed by VSMCs and macrophages and also is associated with apoptosis and plaque vulnerability.…”
Section: Discussioncontrasting
confidence: 66%
“…Actually, kiss1r ‐knockout mice exhibit the phenotypes of glucose intolerance and obesity . KPs also regulate vascular tone as a constrictor . However, in our study, chronic infusion of KP‐10 did not affect body weight, plasma glucose level, and BP in ApoE −/− mice.…”
Section: Discussioncontrasting
confidence: 66%
“…This was detected when KP-13 was applied intraperitoneally in vivo (Qureshi and Kanwal 2011). In our earlier experiments we detected an enhancement of thromboxane (a potent vasoconstrictor and platelet aggregator) synthesis of rat platelets in the presence of KP-13 (Mezei et al 2015). In our present study, we observed that KP-13 enhanced the aggregation of nondiabetic platelets in a dosedependent manner, in the presence of collagen as inducer.…”
Section: Nondiabetic Ratssupporting
confidence: 72%
“…In our earlier experiments, we detected an elevated eicosanoid synthesis of rat platelets in the presence of KP-13 (Mezei et al 2015).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation